Rancang Bangun Sistem Pendukung Keputusan Penempatan Tenaga Pendidik Menggunakan Metode Profile Matching - Agus Nurdianto; Sulis Janu Hartati; Yoppy Mirza Maulana (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Surabaya City Department of Education is the government agencies engaged in the field of education. Field workforce is part of the Department of Education Surabaya handling and placement needs of educators and non-educators to all public schools in the city of Surabaya. The main constraints faced by the Surabaya City Department of Education today is the process of placing an uneven educators based on the subjects required by each school.These constraints lead to uneven educators, resulting in accumulation of educators in some schools. To overcome these obstacles, the required application of Decision Support System Design Placement Educator Profile Matching Method Using. Selection of profile matching method because the method has been shown to result in recommendations for placement in Biereun PTT.Based on the testing that has been done, the application can generate recommendations that will occupy school teacher placement options based on matching of perangkingan owned by each teacher. This application can help Surabaya City Department of Education, particularly the field of workforce to meet the needs of compulsory teaching required and equalization competent educators in each school according to need